2015
DOI: 10.1016/j.neurobiolaging.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein D modulates amyloid pathology in APP/PS1 Alzheimer's disease mice

Abstract: Apolipoprotein D (apoD) is expressed in the brain and levels are increased in affected brain regions in Alzheimer's disease (AD). The role that apoD may play in regulating AD pathology has not been addressed. Here, we crossed both apoD-null mice and Thy-1 human apoD transgenic mice with APP-PS1 amyloidogenic AD mice. Loss of apoD resulted in a nearly 2-fold increase in hippocampal amyloid plaque load, as assessed by immunohistochemical staining. Conversely, transgenic expression of neuronal apoD reduced hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…This transcriptional regulation agrees with a number of widely known correlational studies showing high expression levels of ApoD in many aged model organisms, as well as in humans and rodents suffering from neurodegenerative conditions (reviewed by Dassati et al, 2014;Rassart et al, 2000). In this context, a recent report links ApoD expression levels to the regulation of amyloid plaque pathology in a mouse model of AD (Li et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
“…This transcriptional regulation agrees with a number of widely known correlational studies showing high expression levels of ApoD in many aged model organisms, as well as in humans and rodents suffering from neurodegenerative conditions (reviewed by Dassati et al, 2014;Rassart et al, 2000). In this context, a recent report links ApoD expression levels to the regulation of amyloid plaque pathology in a mouse model of AD (Li et al, 2015).…”
Section: Introductionsupporting
confidence: 87%
“…We have previously analyzed ApoD expression in the nervous system under stress, damage or pathological conditions (Bajo‐Grañeras et al, ; Ganfornina et al, ; Ganfornina et al, ; Garcia‐Mateo et al, ; Li et al, ; Sanchez et al, ), and found that it is up‐regulated in glial cells in both CNS and PNS (reviewed by Dassati, Waldner, & Schweigreiter, ). In the healthy brain, the major cell type expressing ApoD is the mature oligodendrocyte (Supporting Information, Figure S1a and Ganfornina et al, ; Navarro, Del Valle, & Tolivia, ; Ong et al, ; Provost et al, ; Soreq et al, ), and the oligodendrocyte‐specific transcriptome is particularly altered in ApoD‐KO mice (Bajo‐Grañeras et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, DCM contained factors that were related to chemokine signaling and Candidates that are secreted and of interest in these cultures are highlighted in bold and reflect those indicated in Figure 7b 4.4 | Factors found in CCM A2M, a broad spectrum proteinase inhibitor and a carrier of growth factors was increased in CCM. It has been associated with neurological disorders (multiple sclerosis [MS] and AD), other inflammatory diseases of the CNS and nerve injury (Li et al, 2015;Reindl et al, 2001). Apolipoprotein D (ApoD) is a secreted glycoprotein with many roles within lipid transport, detected in neurons, astrocytes, and oligodendrocytes (Ong et al, 1999).…”
Section: Identification Of Mhep Binding-proteins In CM From Mc-inj mentioning
confidence: 99%
“…Apolipoprotein D (ApoD) is a secreted glycoprotein with many roles within lipid transport, detected in neurons, astrocytes, and oligodendrocytes (Ong et al, 1999). It has been associated with neurological disorders (multiple sclerosis [MS] and AD), other inflammatory diseases of the CNS and nerve injury (Li et al, 2015;Reindl et al, 2001). Interestingly levels were not above threshold in MC-Demy, suggesting a nerve damage component to its upregulated expression.…”
Section: Identification Of Mhep Binding-proteins In CM From Mc-inj mentioning
confidence: 99%